Commercial Seaweed Cultivation in Scotland and the Social Pillar of Sustainability: A Q-Method Approach to Characterizing Key Stakeholder Perspectives - Bjørkan, Maiken; Billing, Suzannah-Lynn (Frontiers in Sustainable Food Systems, 2022)
Finding the right way to move forward with seaweed cultivation requires the relevant stakeholders to reach agreement on what goals/limits to set and subsequently what measures should be taken to achieve them. Using a Q-method approach and an analytical framework based on in-put legitimacy and the four pillars of sustainability, we discuss the answers of a diverse set of stakeholders to the question: how should commercial seaweed cultivation in Scotland develop? Our results reveal three main discourses. The first focused on environmental and social sustainability, the second on accessing global markets, economic and environmental sustainability and the third prioritized jobs and social and institutional sustainability. The areas of consensus across the factors included the perception that large-scale and multi-national owned farms are not the ideal model for development of the industry in Scotland. All participants advised that the current regulatory regime for seaweed cultivation requires improvement. These results are discussed within the analytical framework and a prediction of the factors required to establish a legitimate seaweed cultivation industry in Scotland is presented.